Military Leadership : In Pursuit of Excellence. - Taylor,Robert L. & Rosenbach,William E. (Rawalpindi Services Book Club, 2005)
An anthology of classic and contemporary articles, as well as original essays, on leaders, followers, and the personal and organizational values that promote effective military leadership.
Keywords: Military Leadership : In Pursuit of Excellence. -- Militry -- Military art and science -- World politics -- National security